Mo Yan- representative of hallucinatory Realism - Shavkat Hasanov Ahadovich; Boshmanova Dildora Mahramovna (Research Parks Publishing LLC, 2021)
Modern Chinese literature includes the last Ching (1895-1911), the Republican period (1911-1949), Mao (1949-1976), and the Post-Мао (1976 to the present) periods. During the last Ching period, the literature witnessed a mixture of Chinese and Western traditions: topics such as social problems, historical evolution, and changes in ethnic values were covered